PENGARUH PUASA DUA KALI SEMINGGU TERHADAP BERAT TUBUH DAN PERSEN MASSA LEMAK DENGAN PEMANTAUAN MELALUI WHATSAPP DI YOGYAKARTA - Nabawiyah, Hafidhotun; Probosuseno, Probosuseno; Rahmawati, Neni Trilusiana (PERSATUAN AHLI GIZI INDONESIA, 2019)
The incidence of overweight and obesity in Indonesia is experiencing an upward trenin almost all levels of society; overweight women and obesity tend to be more than men. Fasting becomes one of the alternative supporters of a healthy lifestyle to lose weight and body fat mass. Objective of the study was to determine the effect of fasting intermittent twice a week on weight loss by monitoring WhatsApp. Method: Quasi experimental non-randomized pre-post control trial. The study sample was women aged 20 - 46 years who were divided into control group and intervention group. Intervention groups were given intermittent fast twice each week for eight weeks.The research was conducted in Yogyakarta. Results showed there was an average body weight difference of -0.07 ± 1.3 in the control group and -1.74 ± 1.5 in the intervention group with p value 0.97 and 0.00 respectively. Conclusions: There was a significant decrease in the intervention group but no differences in the variable body weight and fat mass between the control group and the intervention group. There is a difference in body weight in the intervention group.